Source for the breeding of soft spring wheat in the conditions of Kirov region - O. S. Amunova; L. V. Volkova; E. V. Zuev; A. V. Kharina (Аграрная наука Евро-Северо-Востока)
In the conditions of the Kirov region, 375 samples of soft spring wheat of various ecological and geographical origin (from 30 countries) of the Federal Research Centre N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) collection were studied. The assessment of the source material by yield, duration of the growing season, plant height, lodging resistance, productivity of the ear and plant, 1000-grain mass is presented in the form of a 9-point system of the severity of the trait for three years of field study. As sources for breeding, varieties that combine high yield (5.0...9.0 points) with a high level of economically valuable traits (7.0...9.0 points) were identified. The maximum average point (9.0) for yield capacity was noted by the variety Karabalykskaya 91 (Kazakhstan). The optimal height (53.9...74.0 cm) and lodging resistance were noted in the varieties: Estivum 155 (Russia), Kvorum (Ukraine), Epos, Ethos, Nandu, Schenk and KVS Akvilon (Germany), AC Phil and PT-741 (Canada), Hybrid (Mexico), Leguan (Czech), PS-133 (China) and SSL 25-2 (USA). Early maturation was distinguished in the domestic varieties Skala and Iren (80...87 days). The samples Line 3691h, Izida, FPCh-Ppd-m, Gerakl, Sibirskaya 16 (Russia), Kvorum (Ukraine), Attis and Nandu (Germany), Musket (England) were distinguished by the length (7.3...8.8 cm) and the number of grain of the main ear (32.1...39.9 pcs.). The varieties Voronezhskaya 16, Gerakl, Saratovskaya 72, Saratovskaya 73, Sibirskaya 16, Serebristaya, FPCh-Ppd-m and Ekada 6 (Russia), Anshlag and Kvorum (Ukraine), AC Gabrieland Hoffman (Canada), Attis and Nandu (Germany) were distinguished by a high grain weight per ear (1.28...1.58 g). The varieties Zakamskaya (Russia), Rassvet (Belarus), AC Cadillac (Canada) and PS-95 (China) are recommended as sources of high protein content. It is shown that the wheat yield in the region is closely related to the plant height (r = 0.67), the ear and plant productivity elements (r = 0.24...0.41), the protein content (r = -0.49) and does not depend on the 1000-grain mass (r = 0.04). Sixteen samples were identified with complex resistance to dominating fungal diseases. Samples Altajskaya 110, Kinelskaya 61, Line 2, Lutescens 30 and Estivum V313 (Russia) combined high yield with aluminum resistance. Varieties Altajskaya 100, Baganskaya 95, Line 3691h, Novosibirskaya 20 and Estivum 155 (Russia), Klein Vencedor (Argentina) and NOS Norko (Germany) were characterized by high yield and drought resistance. Based on the obtained results, a bank of sources of economically valuable traits was created, which allows to involve genotypes adapted to the conditions of the region in the breeding process.